Species of Astrothrips from China, with one new species and a list of plant associations (Thysanoptera, Panchaetothripinae) - Li, Yajin; Mound, Laurence A.; Xie, Yanlan; Zhang, Hongrui (Zootaxa, 2021)
Seven species of the Panchaetothripinae genus Astrothrips are recorded from China, and an illustrated key provided for their identification. One new species is described, A. glanduculus sp.n., and the following three species are newly recorded from China, A. asiaticus, A. globiceps, and A. tumiceps. The male of A. aucubae is described for the first time, and plants from which Astrothrips have been taken are listed.